Determinación de la potencia antimicrobiana por el método Turbidimétrico. Antimicrobial potency assessment using the turbidimetric method. - Marmolejo- Ruíz , G.S.,; Alba-Romero , J.J.,; Rico-Del Rio , A.E.,; Lozano-Morán , M.,; Martínez-Romero , A.,; Téllez-López , M.Á.,; Hernández-González , S.I. (Revista de Ciencias Médicas Torreón, 2026)
The pharmaceutical industry is an essential sector within lifescience, facilitating the development of new drugs andtechnologies aimed at human and animal health. The qualityof pharmaceutical products must be guaranteed throughsystematic evaluation processes that ensure both theirefficacy and safety; in this context, the assessment ofmicrobiological methods becomes an essential componentwithin the quality control laboratory. The objective of thisresearch was to determine the antimicrobial potency of aninjectable pharmaceutical product with oxytetracycline as theactive ingredient using the Turbidimetric method, as well asto design and validate the methodology. The methodologyused refers to the general analysis method 0100,microbiological assay of antibiotics from the MexicanPharmacopoeia. In this study, the antimicrobial potencyobtained for the veterinary injectable pharmaceutical productwith Oxytetracycline was 109.91%, which is acceptable. Thisresult confirms that the drug inhibits the growth of the testmicroorganism, Staphylococcus aureus (ATCC 29373). Byimplementing this validated method, the reliability of theresults is guaranteed.